Sequencing effects of balance and plyometric training on physical performance in youth soccer athletes - Hammami, R.; Granacher, U.; Makhlouf, I.; Behm, D. G.; Chaouachi, A. (The Journal of Strength and Conditioning Research, 2016)
Balance training may have a preconditioning effect on subsequent power training with youth. There are no studies examining whether the sequencing of balance and plyometric training has additional training benefits. The objective was to examine the effect of sequencing balance and plyometric training on the performance of 12- to 13-year-old athletes. Twenty-four young elite soccer players trained twice per week for 8 weeks either with an initial 4 weeks of balance training followed by 4 weeks of plyometric training (BPT) or 4 weeks of plyometric training proceeded by 4 weeks of balance training (PBT). Testing was conducted pre- and posttraining and included medicine ball throw; horizontal and vertical jumps; reactive strength; leg stiffness; agility; 10-, 20-, and 30-m sprints; Standing Stork balance test; and Y-Balance test. Results indicated that BPT provided significantly greater improvements with reactive strength index, absolute and relative leg stiffness, triple hop test, and a trend for the Y-Balance test (p = 0.054) compared with PBT. Although all other measures had similar changes for both groups, the average relative improvement for the BPT was 22.4% (d = 1.5) vs. 15.0% (d = 1.1) for the PBT. BPT effect sizes were greater with 8 of 13 measures. In conclusion, although either sequence of BPT or PBT improved jumping, hopping, sprint acceleration, and Standing Stork and Y-Balance, BPT initiated greater training improvements in reactive strength index, absolute and relative leg stiffness, triple hop test, and the Y-Balance test. BPT may provide either similar or superior performance enhancements compared with PBT.